2022
DOI: 10.1002/suco.202200083
|View full text |Cite
|
Sign up to set email alerts
|

Performance‐based design method for isolated hollow RC piers with irregularity in height

Abstract: The bridge piers are the main components, and their destruction can cause significant damage to bridges. The concentration of failure in one or two piers of irregular bridges has led to challenges in codes and studies regarding the simultaneous failure of the substructure components. The RC hollow sections are structurally adequate for application in isolated bridges with unequal pier heights due to their large strength/mass and stiffness/mass ratios. In the previous studies, the isolation devices have been us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…The obtained results showed that the structural characteristics significantly impacted the seismic vulnerability of the studied bridges [28]. Rasouli et al [29] proposed a performance-based design method for continuous span bridges with unequal height isolated hollow RC piers. The outcome of this study showed that the characterisitcs of pier cross section and Lead Rubber Bearings (LRBs) are important factors to achieve a uniform ductility demand and performance level in all piers.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results showed that the structural characteristics significantly impacted the seismic vulnerability of the studied bridges [28]. Rasouli et al [29] proposed a performance-based design method for continuous span bridges with unequal height isolated hollow RC piers. The outcome of this study showed that the characterisitcs of pier cross section and Lead Rubber Bearings (LRBs) are important factors to achieve a uniform ductility demand and performance level in all piers.…”
Section: Introductionmentioning
confidence: 99%